Life as art : the biographical writing of Hazel Rowley - Rowley, Hazel (Melbourne University Publishing, 2021)
'My books are all, in their different ways, voyages of discovery. I write books to learn, to stretch my horizons. These voyages of mine are full of risk and passion.' Hazel Rowley Hazel Rowley was an award-winning biographer who was committed to telling the stories of people's lives. This collection of short pieces--journal articles, essays, talks, diary entries - provides a wonderful insight into her craft. In these pages she talks honestly about the joys, the challenges, the highs and the lows of writing biography. Much of the material is previously unpublished and reveals Rowley's lively ideas on a range of topics. Before her untimely death in 2011, Rowley wrote four acclaimed biographies: about Christina Stead, Richard Wright, Simone de Beauvoir and Jean-Paul Sartre, and Franklin and Eleanor Roosevelt. This new collection gives a rich store of reflections on biography and draws the reader into Rowley's passionate pursuit of stories and her search for new biographical subjects. Della and Lynn, along with Hazel's friend Irene Tomaszewski, established the Hazel Rowley Literary Fellowship in her memory.
Keywords: Rowley, Hazel.; Stead, Christina, -- 1902-1983.; Wright, Richard, -- 1908-1960.; Beauvoir, Simone de, -- 1908-1986.; Sartre, Jean-Paul, -- 1905-1980.; Roosevelt, Franklin D. -- (Franklin Delano), -- 1882-1945.; Roosevelt, Eleanor, -- 1884-1962.; Authors -- Biography.; Biographers -- Australia.; Biography as a literary form.; Biography -- 20th century.; Philosophers -- France -- Biography.; Presidents' spouses -- United States -- Biography.; Presidents -- United States -- Biography.; Women biographers -- Australia.; Biography.; Biography: general.; Écrivains -- Biographies.; Biographes -- Australie.; Biographie (Genre littéraire); Biographies -- 20e siècle.; Philosophes -- France -- Biographies.; Femmes biographes -- Australie.; Biographies.; biographies (literary genre); biography (general genre); BIOGRAPHY & AUTOBIOGRAPHY / Literary; Authors.; Biographers.; Philosophers.; Presidents' spouses.; Presidents.; Women biographers.; Australia.; France.; United States.; 1900-1999